LOCAL MOMENT FORMATION IN DISORDERED-SYSTEMS - A LOW-FILLING QUASI-ATOMIC LIMIT - Siringo, F; Logan, D (1991)
Using a self-consistent mean-field approach to a disordered Hubbard model the authors show that, regardless of the role of correlation in the half-filled band for which the conventional phenomenology is recovered, correlation effects can be strongly enhanced by disorder in the low-filling limit, leading to a well-defined quasi-atomic domain of strong local moments on an inhomogeneous scale. They argue that the theory provides a natural origin for the observed behaviour of the Cs-rich liquid alloys Cu-Au close to stoichiometry.